Analisis Peran Bundo Kanduang dalam Keterwakilan Perempuan di Kabupaten 50 Kota, Sumatera Barat - Jalius, As'ad Albatroy (FISIP Universitas Tanjungpura, 2023)
This research provides an overview of a study that investigates the role of Bundo Kanduang in enhancing women's representation and empowerment in the 50' Kota Regency of West Sumatra, Indonesia. Bundo Kanduang is a traditional Minangkabau institution that plays a significant part in the social, cultural, and political life of the Minangkabau community. This research delves into the ways in which role's Bundo Kanduang has influenced the participation of women at that regency. The study employs qualitative research methods, including interviews, focus group discussions, and document analysis, to collect data on the experiences and perspectives of women in the 50' Kota Regency. The research explores the historical development of Bundo Kanduang, its organizational structure, and its contemporary role in women's lives. Preliminary findings suggest that Bundo Kanduang has evolved over time, adapting to changing cultural and political contexts. It has played a crucial role in preserving Minangkabau cultural traditions and promoting women's involvement in decision-making processes at the community level. However, it also faces challenges and criticisms, particularly related to its they roles in gender isue. the research project aims to provide a more comprehensive understanding of Bundo Kanduang's impact on women's lives and the potential for future improvements in women's representation and empowerment.